detaylı cevap lütfen
![Detaylı Cevap Lütfen class=](https://tr-static.eodev.com/files/dfa/aa4fe41985b0da7741084c22a1f0784c.jpg)
Adım adım açıklama:
[tex] \frac{(a - 2)(c - 4)}{(b + 2)} = k[/tex]
şeklinde olacaktır.
a=6
b=2
c=9 için.
[tex] \frac{4.5}{4} = 5[/tex]
[tex]k = 5[/tex]
b=8, c=6 için,
[tex] \frac{(a - 2).2}{10} = 5[/tex]
[tex]2(a - 2) = 50[/tex]
[tex]a - 2 = 25[/tex]
[tex]a = 27[/tex]
Cevap:
Cevap E
Adım adım açıklama:
[tex] \frac{(a - 2).(c - 4)}{b + 2} = \frac{(6 - 2).(9 - 4)}{(2 + 2)} \\ = \frac{4.5}{4} \\ = \frac{20}{4} \\ = 5[/tex]
[tex] \frac{(a - 2).(6 - 4)}{(8 + 2)} = 5 \\ \frac{(a - 2).2}{10} = 5 \\ (a - 2).2 = 10.5 \\ (a - 2).2 = 50 \\a - 2 = \frac{50}{2} \\ a - 2 = 25 \\ a = 27[/tex]
~Başarılar...